THE CITIZENS’ PARTICIPATION IN THE DEVELOPMENT OF PUBLIC POLICIES AS A WAY OF CONTINUOUS ADAPTATION OF THE ADMINISTRATIVE ACTION TO SOCIETAL CHANGES AND THE CHALLENGES OF ITS IMPLEMENTATION - Danelciuc-Colodrovschi, Natașa (International Journal of Legal and Social Order, 2024)
The object of the study is to analyze the importance of the development of participatory mechanisms for a better adaptation of the administrative action to the citizens’ needs and expectations. The author examines the legal framework of several countries in order to assess the level of compliance with European standards